CLINICAL AND ANAMNESTICAL FEATURES OF JUVENILE CHRONIC ARTHRITIS IN THE REPUBLIC OF BURYATIA - L. V. Zhdanova (Acta Biomedica Scientifica)
Article is devoted to the study of the epidemiology of juvenile arthritis in children in the Republic of Buryatia. All-Russian register of juvenile arthritis (JA) by the Republic of Buryatia (RB) is 48 patients aged 10,2 ± 5,1 years, with a mean disease duration of 3,4 ± 3,2 years, including 26 boys and 22 girls. There is a high incidence of JA in the Republic of Buryatia, which is 21,2 to 100,000 child population. Age of onset of the disease falls on school years and is 7,1 ± 4,5 years. Marked the beginning of the peak age 2 JA: 1-3 years 31,2 %, and 8-12 years 39,5 %. In 66,6 % of cases occur oligoarticular form JA. More than half of patients have extra-articular manifestations of JA, the majority of which occur in the reaction of lymphoproliferative (lymphadenopathy, hepatosplenomegaly). 56,2 % of patients with JA have a disability, 70 % of it is set in the first year of the disease. 90 % of patients with JA being treated with methotrexate, of whom 69 % are on conjoint immunosuppressive therapy, including 13 % genetically engineered biological agents.